Diagnostic Value of Diurnal Variability of Orthostatic Heart Rate Increment in Children and Adolescents With POTS - Cai, Hong; Wang, Shuo; Zou, Runmei; Li, Fang; Zhang, Juan; Wang, Yuwen; Xu, Yi; Wang, Cheng (Frontiers in Pediatrics, 2021)
Objectives: To investigate the diurnal variability of heart rate (HR) increment after standing (ΔHR) in pediatric postural tachycardia syndrome (POTS), and explore appropriate cutoff values of ΔHR at different times for the POTS diagnosis. Materials and Methods: 78 patients (9-14 years) presented with orthostatic intolerance symptoms were enrolled. 43 patients were diagnosed as POTS (ΔHR ≥ 40 bpm), and 35 patients were assigned to the non-POTS group (ΔHR < 40 bpm). 26 healthy children served as a control group. All subjects completed 3 standing tests in the morning, afternoon and evening. Orthostatic HR parameters were analyzed to predict the diagnosis of POTS. Additionally, 41 patients were recruited as an external validation group. Results: Orthostatic HR increments in both POTS and non-POTS groups exhibited diurnal variability, which was markedly larger in the morning (P<0.05), while did not differ with the time of day in the control group. Among the POTS patients, 100% met the diagnostic criteria for POTS in the morning, 44.2% in the afternoon, 27.9% in the evening. Almost half of the POTS patients (51.2%) displayed a positive result only in the morning standing test. However, in the 3 standing tests at different times, ΔHR from 1 min to 10 min after standing and ΔHRmax were highest in the POTS group than in the non-POTS and control groups (P < 0.05). Furthermore, the maximum ΔHR (ΔHRmax) and ΔHR at 5 min and 10 min in the afternoon and evening standing tests yielded moderate predictive values for the POTS diagnosis. The external validation test showed that the afternoon ΔHRmax ≥ 30 bpm to diagnose POTS yielded sensitivity, specificity, and accuracy of 85%, 71.4%, and 78%, respectively; and the evening ΔHRmax ≥ 25 bpm yielded sensitivity, specificity, and accuracy of 85%, 76.2%, and 80.5%, respectively. Conclusions: The orthostatic HR increment exhibits diurnal variability in children and adolescents with POTS which may affect the diagnosis of POTS. Supplementary criteria are proposed for the POTS diagnosis based on diurnal variability.